HUBUNGAN FUNGSI ORGANIZING KEPALA RUANG DENGAN PENERAPAN PATIENT SAFETY DI RUANG RAWAT INAP RUMAH SAKIT TINGKAT III BALADHIKA HUSADA JEMBER: Relationship Between the Organizing Function of the Head Nurse with the Implementation of Patient Safety in the Inpatient Room of Level III Hospital Baladhika Husada Jember - Afandi, Fizal; Asmuji; Haryandi, Dwi Yunita (Forind Press, 2024)
Patient safety is indispensable in efforts to improve hospital quality. Leadership has a positive impact on nurse motivation and improves safety rates. Ineffective leadership support is three times more likely to implement poor patient safety. The successful implementation of patient safety in nursing is strongly supported by the role and function of the room manager through the organizing function of nursing services in the inpatient room, in this case the researcher is interested in conducting research on the relationship between the organizing function of the head of the room with the implementation of patient safety in the Inpatient Room of Level III Baladhika Husada Jember Hospital. This study uses a correlation design with a cross-sectional approach that aims to see if there is a relationship between the organizing function of the head of the room with the implementation of patient safety. The population of this study were nurses who worked in the Inpatient Room of Level III Baladhika Husada Jember Hospital with a total of 74 nurses consisting of 18 D3 graduates and 56 Ners graduates. The sampling technique used proportionate stratified random sampling. Assessment using questionnaires related to organizing functions and implementation of patient safety. The results of the study with the Spearman Rho Rank test (a = 0.05) obtained a p value of (p = 0.00) which means that there is a significant relationship between the organizing function of the head of the room with the implementation of patient safety. The conclusion of this study is that there is a significant relationship between the organizing function of the head of the room and the implementation of patient safety.